Public Health and Behavioral Economics. “Nudging” Behaviors Through Wearable Technology - Neațu, Alina Maria (International Journal of Economic Practices and Theories, 2015)
Public health has always been a matter of great concern for a great number of stakeholders, such as: governments, ministries, health groups, non-governmental organizations, political leaders, private partners, health professionals or various business communities. Long-term improvements in the overall health and wellbeing of the population can now be more easily achieved by encouraging people towards a healthier, more active life-style using innovative prevention and monitoring tools and technologies. Among many other given benefits, wearable technology entails the potential to deliver public health support on a previously unimaginable scale, for example by helping individuals autonomously manage their eating, sleeping and physical activity and reducing pressure on their personal health and the healthcare systems created to support them. Behavioral economics provides the means to potentially increase awareness, reduce disparities, inform people and motivate them in this regard. Focusing on the relatively predictable mind paths and mental shortcuts (heuristics) humans employ to make decisions, the emerging field of behavioral economics can provide valuable insights for policy makers when developing strategies to motivate people in leading a healthier life. The present paper describes how several behavioral economic principles in decision-making can influence health attitudes and behaviors and what are some of the most useful and appealing wearable technologies in 2015, that health practitioners and private individuals can employ and promote when considering health improvement, monitoring and feed-back. The research concludes with summarizing downsides, awareness, technical challenges, acceptance and implementation of modern wearable technologies in day-to-day life, also proposes various recommendations and future research questions to urge this promising area of research and practice.